2007
DOI: 10.1584/jpestics.g07-08
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of transgenic rice plants expressing a novel mutated ALS gene of rice

Abstract: We performed functional analysis of transgenic plants expressing the W548L/S627I mutated ALS gene from rice as well as studies on inheritance of the mutated gene, phenotype and fertility of transgenic plants to ensure availability of the mutated gene as a selectable marker for plant genetic transformation. Expression levels of the ALS (endogenousϩmutated ALS) gene of transgenic rice plants were correlated with the resistance of transgenic plants to bispyribac-sodium (BS). The BS-resistant trait of a transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…We have isolated a double-mutated ALS gene from rice cells (OsALS-W548L/ S627I) (Figure 2), which confers a high level of resistance to the PC-type ALS-inhibiting herbicide bispyribac-sodium (BS) (Figure 1), and demonstrated that it could be used as a selectable marker for generating transgenic rice plants (Kawai et al, 2007a;Kawai et al, 2007b). We also found that the single amino acid substitution S627I in the ALS gene (OsALS-S627I) imparts high levels of resistance to the PCs pyrithiobac-sodium (PS) and pyriminobac (PM).…”
Section: Als Mutations Interfering With Herbicide Actionsmentioning
confidence: 99%
“…We have isolated a double-mutated ALS gene from rice cells (OsALS-W548L/ S627I) (Figure 2), which confers a high level of resistance to the PC-type ALS-inhibiting herbicide bispyribac-sodium (BS) (Figure 1), and demonstrated that it could be used as a selectable marker for generating transgenic rice plants (Kawai et al, 2007a;Kawai et al, 2007b). We also found that the single amino acid substitution S627I in the ALS gene (OsALS-S627I) imparts high levels of resistance to the PCs pyrithiobac-sodium (PS) and pyriminobac (PM).…”
Section: Als Mutations Interfering With Herbicide Actionsmentioning
confidence: 99%
“…We have also shown that a transgenic rice plant into which this double-mutated ALS gene was introduced expressed resistance to BS. 2,3) Herbicide-resistant ALS genes have been shown to be useful not only for the generation of transgenic plants that express resistance to the corresponding herbicides but also for introducing foreign traits into plants as a selectable marker. 4) Indeed, the W548L/S627I double-mutated ALS gene was shown to be useful as a selectable marker for plant genetic transformation when used together with BS.…”
Section: Introductionmentioning
confidence: 99%
“…A two-point mutated rice ALS gene, OsALS (dm), was created when two-point mutations, W548L and S627I, in the OsALS gene were introduced by site-directed mutagenesis. The OsALS ( d m ) g e n e w a s i n t r o d u c e d i n t o r i c e b y Agrobacterium-mediated transformation (Kawai et al, 2007a). After spraying over the leaves and stems of transgenic rice carrying the OsALS (dm) gene, they grew normally, indicating that the OsALS (dm) gene acted functionally in rice plants.…”
Section: A Two-point Mutated Rice (Oryza Sativa L) Als Gene Conferrementioning
confidence: 99%
“…We introduced the OsALS (dm) gene into turf-type tall fescue to confer herbicide resistance using Agrobacterium-mediated transformation (Sato et al, 2009). Agrobacterium tumefaciens strain EHA105 carries the binary vector pMLH7133-OsALS (dm) consisting of the OsALS (dm) gene and hygromycin phosphotransferase gene (hpt) under the control of the enhanced cauliflower mosaic virus (CaMV) 35S promoter (Kawai et al, 2007a). Embryogenic calli were induced from shoot tips of the turf-type tall fescue cultivar Tomahawk germinated in vitro.…”
Section: Production Of Transgenic Herbicide-resistant Tall Fescue Formentioning
confidence: 99%